Leaf Anatomical Modification in Drought of Rice Varieties (Oryza sativa L.) - Anggara Dwi Putra Zagoto; Violita Violita (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2019)
Each organ plant has been formed perfectly to support physiological processes in an unfavorable environmental condition. Rice (Oryza sativa L.) be included plants sensitive to drought conditions during a stage of growth and development. This will cause pressure (stress) resulting in a decrease in rate metabolism in leaf cells. Leaf anatomical characteristics are criteria that can be used to identify plants that are tolerant to drought. Anatomical response leaves in drought conditions inform the development of leaf photosynthetic parts carrying out changes in anatomical structure morphology includes changes in cell walls, organ size, changes in direction growth, including dropping leaves and enhancing the life cycle. The research aimed to determine the anatomic response leaves rice varieties (Oryza sativa L.) to drought stress. Five rice varieties used were given drought-stress treatment for 12 days. Identification leaf anatomical structures using microscopic slices of transverse was made according to the paraffin method. Changes in the anatomical structure of leaves of drought-stress have decreased bulliform cells increase in size, the thickness epidermis cells in an effort to retain the water content in cells, and reducing the size and total stomata with purpose process control flow of transpiration and water use efficiency.